Imágenes Jóvenes. - Selles Ferrando, Xavier (Wien : Fotogalerie Wien, 1996)
Bagué, Tina ; Gómez Fontecha, Silvia ; Huelva, Juan Jesus ; Leo, Jana ; López de la Casa, Paulina ; Martinez Garrote, Margarita ; Matesanz, Rosa ; Mateu, Salva ; Mota, Jesus Jaime ; Muñoz Molina, José Antonio ; Ortiz, Diego ; Pey, Vanessa ; Salvans, Txema ; Sanz, Andrés ; Weil, Alejandra
biog., tent. [2 p.]
Imágenes Jóvenes, Fotogalerie Wien, 6. Juni - 29. Juni 1996
Duits
kunstcatalogus
Keywords: Spanje